Ovarian mass lesions: evaluation of ultrasound guided fine needle aspiration cytology with histopathological correlation - Dr. Majal Shah; Dr. Nisha Khanna; Dr. Trupti Patel; Dr. Dhaval Jetly; Dr. Biren Parikh; Dr. Brinda Chandibhamar (Tropical Journal of Pathology and Microbiology, 2018)
Background: Ovarian masses are frequent finding in females of reproductive age group. Image-guided fine-needle aspiration cytology (FNAC) of ovarian lumps is being increasingly used for the successful diagnosis of ovarian tumors, although borderline cases may be difficult to diagnose by this method. Objective: The present study was performed to evaluate the role of US-guided FNAC in pre-operative cytological diagnosis of ovarian masses in comparison with histopathology and to assess the pitfalls and limitations of cytological interpretation. Materials and Methods: The study was conducted on 160 female patients. Diagnosis was established by FNAC performed under image guidance (ultrasonography/computed tomography) followed by histopathological examination. Cytologic diagnoses were compared with the histopathological diagnosis. Results: On cytology and histopathology comparison, concordance was found to be 90.4% in case of malignancy, 94% in cases of suspicious for malignancy, 100% in cases of inflammatory lesions, 50 % in cases of metastasis. Chi-square test was performed and p value was statistically significant (p < 0.0001). Conclusion: USG-guided FNAC seems to be a relatively safe, simple, fast and cost-effective procedure where most ovarian malignancies either present late in their course or no screening method is available. In addition this procedure may be useful in deciding management guidelines prior to any surgical intervention.